Mass Comparison of Protoplanetary Disk and Planetary Systems - Terluk, Aldana; Gil-Hutton, Ricardo (Earth and Planetary Science, 2025)
In recent decades, the number of discovered exoplanets has increased significantly and is expected to continue growing due to advancements in detection methods. Simultaneously, the study of protoplanetary disks has enabled the estimation of dust mass in various star-forming regions. Since these disks serve as the birthplace of planetary systems, a combined analysis of exoplanets and disks can improve our understanding of planet formation and evolution. In this paper we compare existing estimates of dust mass in protoplanetary disks with the solid mass in known exoplanetary systems to estimate the initial solid mass required to form the observed population of planets. First, the total masses of exoplanetary systems are calculated and these values are then compared with the estimated dust mass in protoplanetary disks. The results indicate that in most cases the solid mass of exoplanetary systems exceeds the expected mass of their original disks. Furthermore, it is found that early-stage disks (Class 0 and Class I) may contain approximately 100 times more dust than those in more evolved stages (Class II). Finally, the results obtained also suggested that the solid mass of observed planetary systems could be limited to a maximum of 500 M⨁, which may constrain the growth of rocky planets and the accumulation of material in the cores of giant planets. ER